Analisis Penambahan Paku Terhadap Kuat Tarik Belah Dan Kuat Lentur Beton - Samma, Yandri Liling; Setiawan, Arman; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Along with the development of technology and increasingly complex construction needs, the use of concrete is growing and becoming increasingly important in infrastructure development. One innovation to improve the quality of concrete is by adding additives or substitute materials to concrete. But concrete still has many weaknesses, especially in tensile and flexural strength, therefore the use of fibers such as nails or steel fibers in concrete is expected to be able to overcome these problems. In this study, a normal concrete compressive strength design of 25 MPa was used with the aim of the study to obtain the effect of nails on the tensile strength and flexural strength of concrete. In this study, the percentage of added nails was 2%, 4%, 6%, 8%, 10% of the weight of the concrete. This study shows that the use of nails in concrete causes an increase in tensile strength and flexural strength in nail variations of 2%, but the use of nails with variations of 4%, 6%, 8% and 10% decreases tensile and flexural strength. Increased tensile strength and flexural strength in nail variations of 2% with values of 3.06 Mpa and 5.67 Mpa. This shows that the greater the addition of nails, the tensile and flexural strength achieved decreases.